The perfect horse : the daring rescue of horses kidnapped during World War II - Letts, Elizabeth (Yearling, 2020)
When American troops learned that the Nazis kidnapped the world's finest horses during WWII, they set out on a rescue mission in the hopes of preventing them from being slaughtered by Russian troops for food. Includes a map and archival photographs.